2017
DOI: 10.1590/1519-6984.172601
|View full text |Cite
|
Sign up to set email alerts
|

Metazoan parasites of the lambari Astyanax altiparanae collected in the Batalha River, State of São Paulo, Brazil

Abstract: Here we conduct a qualitative and quantitative analysis of ectoparasites and endoparasites of Astyanax altiparanae (Garutti & Britski, 2000), popularly known as lambari-do-rabo-amarelo collected from the Batalha River, State of São Paulo, Brazil. Of the 67 specimens of A. altiparanae, 52 were parasitized by at least one parasitic metazoan species. The following metazoan parasites were found: Monogenea, Digenea and Nematoda. The monogenetic Diaphorocleidus sp. was the predominant species, presenting a higher fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…The species Anacanthorus sp., Nothogyrodactylus sp., G. trairae, Bucephalidae gen. sp., A. mordax, Tylodelphys sp., and Eustrongylides are being reported in the Batalha River for the first time, a finding which expands the geographic distribution of these parasites and contributing to the global biodiversity inventory of fish parasites ( Leite 2017, Negrelli et al 2018, Pelegrini et al 2018).…”
Section: Discussionmentioning
confidence: 79%
“…The species Anacanthorus sp., Nothogyrodactylus sp., G. trairae, Bucephalidae gen. sp., A. mordax, Tylodelphys sp., and Eustrongylides are being reported in the Batalha River for the first time, a finding which expands the geographic distribution of these parasites and contributing to the global biodiversity inventory of fish parasites ( Leite 2017, Negrelli et al 2018, Pelegrini et al 2018).…”
Section: Discussionmentioning
confidence: 79%
“…was not reported by the same research group in a revision about parasites of characiforms from the Batalha River collected at a concomitant period, with the specimens analysed by Negrelli et al . (2017) (see Dias et al ., 2017 and references therein). In their checklist, the authors reported the occurrence of Trinibaculum altiparanae (Abdallah, Azevedo & Silva, 2013) instead of Trinigyrus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Negrelli et al . (2017) reported the occurrence of Trinigyrus sp. parasitizing the gills of Astyanax lacustris (Lütken, 1875) (= Astyanax altiparanae Garutti & Britski, 2000) from the Batalha River, State of São Paulo, Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…Astyanax lacustris (Lütken, 1875) (= Astyanax altiparanae ), popularly known as “tambiú” or “lambari-do-rabo-amarelo” is a small characid widely distributed in South America ( Froese & Pauly, 2022 ), inhabiting different freshwater environments ( Negrelli et al, 2018 ) in the Paraná River basin ( Langeani et al, 2007 ) and the lower Iguaçu basin ( Daga et al, 2016 ). This fish species is considered a generalist omnivore ( Negrelli et al, 2018 ) and is known for its successful environmental colonization, due to its opportunistic habits and reproductive strategies, including being able to grow quickly, mature early, and spawn more than once a year ( Sabbag et al, 2011 ). In addition, A. lacustris is economically valuable, being used for human consumption and as live bait for the sport fishing of carnivorous fish ( Sabbag et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%